Long Noncoding RNA and Circular RNA: Two Rising Stars in Regulating Epithelial-Mesenchymal Transition of Pancreatic Cancer - Yang, Xiaoying; Qin, Cheng; Zhao, Bangbo; Li, Tianhao; Wang, Yuanyang; Li, Zeru; Li, Tianyu; Wang, Weibin (Frontiers in Oncology, 2022)
Pancreatic ductal adenocarcinoma (PDAC) is a highly malignant tumor with especially poor prognosis. However, the molecular mechanisms of pancreatic oncogenesis and malignant progression are not fully elucidated. Epithelial-mesenchymal transition (EMT) process is important to drive pancreatic carcinogenesis. Recently, long noncoding RNAs (lncRNAs) and circular RNAs(circRNAs) have been characterized to participate in EMT in PDAC, which can affect the migration and invasion of tumor cells by playing important roles in epigenetic processes, transcription, and post-transcriptional regulation. LncRNAs can act as competing endogenous RNAs (ceRNA) to sequester target miRNAs, bind to the genes which localize physically nearby, and directly interact with EMT-related proteins. Currently known circRNAs mostly regulate the EMT process in PDAC also by acting as a miRNA sponge, directly affecting the protein degradation process. Therefore, exploring the functions of lncRNAs and circRNAs in EMT during pancreatic cancer might help pancreatic cancer treatments.